COMPARATIVE ANALYSIS OF SORTING ALGORITHMS USED INCOMPETITIVE PROGRAMMING - Mamatnabiyev, Zh.; Zhaparov, M. (Journal of Emerging Technologies and Computing, 2024)
Sorting is one of the most used and fundamental operation in computer science since the first time it had been tried to arrange list of items insome sequence. A large number of sorting algorithms were designed in order to have best performance in terms of computational complexity, memory usage, stability, and methods. In addition, in algorithmic problem solving, not all algorithms have same efficiency. This paper makes comparison research and discusses four different types of sorting algorithms: bubble sort, quick sort, insertion sort, and merge sort. The algorithms are tested and compared for data usage and time spent for sorting given amount of data.